The Influence of Tyroxine Hormone on Megami Pellet Feed Against the Growth of Cantang Grouper (Epinephelus fuscoguttatus-lanceolatus) Cantang Grouper (Jurnal Intek Akuakultur, 2018)
Grouper E. fuscoguttatus-lanceolatus is one type of marine fish that is economically valuable and can be developed into a promising cultivation commodity. The problem of E. fuscoguttatus-lanceolatus cultivation is the growth of fish that is still classified as slow so that encourage researchers to conduct study related to the effect of giving of tiroksin in pellet feed. Results There was no significant effect of thyroxine hormone treatment on growth of length, weight, and daily weight of grouper E. fuscoguttatus-lanceolatus. However, based on statistical test the research data showed no significant differences in growth of length, weight, and daily weight in each hormone treatment. The success rate of E. fuscoguttatus-lanceolatus E. fuscoguttatus-lanceolatus is high, and the mortality rate is low. The highest treatment dose on long growth rate of fish and weight addition and daily growth of grouper E. fuscoguttatus-lanceolatus cantang at the treatment of 0.6 mg / kg-feed